Steroidal Glycosides from Reineckia carnea herba and Their Antitussive Activity - Han, Na; Chen, Ling Li; Wang, Yao; Xue, Rui; Zou, Li Bo; Liu, Fang; Yin, Jun (Planta Medica, 2013)
Two new steroidal glycosides, 1α,3α-dihydroxy-5β-pregn-16-en-20-one 3-O-α-L-rhamnopyranoside (1) and 1β,3β,27-trihydroxycholest-16-en-22-one 1,3-di-O-α-L-rhamnoside (2), along with seven known steroidal glycosides (3–9), were isolated from Reineckia carnea herba. Their structures were determined by detailed analysis of their 1D- and 2D-NMR and MS spectra. Compound 9 was isolated for the first time from the Reineckia genus. Except for 8, compounds 2, 3, 4, 5, 6, 7, and 9 displayed clear in vitro antitussive activity.
Keywords: Reineckia carnea; Liliaceae; steroidal glycosides; antitussive